Appraising the Role of the Individual in Political and Social Change Processes: Jung, Camus, and the Question of Personal Responsibility–Possibilities and Impossibilities of "Making a Difference". (27th August 2014) - Samuels, Andrew
ABSTRACT The paper is an attempt to open discussion on the role of "the individual" in contemporary progressive and radical political discourse and criticism. Academic stress on the contexts in which individuals operate, while necessary and useful, cuts us off from sources for thinking about such a role. Jung's ideas about the relations of individual and social/collective are important and suggestive yet require extensive revision. Camus's book The Rebel is useful in making such revisions. Centrally, the paper proposes new thinking about "broken" and "fractured" individuals as it probes the limits of personal responsibility. Questions of individual political "type" or "style" are posed, intended to provide a novel account of how political attitudes, engagements and behaviours may be conceptualised. Copyright © 2014 John Wiley & Sons, Ltd.